Selametan Day of the Dead From a Javanese Cultural Perspective among Santri and Abangan: a Case Study in Tulungagung District - Bagus Wahyu Setyawan; Abd. Aziz; Teguh Teguh; M. Jazeri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
Selametan (communal feast) is tradition to commomerate one’s death day conducted by the Javanese community. Its implementation is different from one region to others. The study focused on describing and explaining the differences of selametan between santri and abangan community. It was a field study carried out in Tanen Village, Rejotangan District, Tulungagung Regency. The data were obtained by conducting an observation to the Tanen community. Besides, the data were also collected through interview and literature study. The results indicate that there are two versions of implementing the selametan tradition in Tanen Village. The abangan version still maintains traditions from the ancestors, in terms of using sesajen (offering) as a cultural symbol and means in a ritual. The time also remains the same as inherited from the ancestors, in which the ritual is conducted from the first day until nyewu dina or 1000 th day. The santri version only conducts the selametan tradition from the first until seventh days after the funeral and does not use sesajen considering its inappropriateness with Islamic lessons. Apart from these differences, the selametan tradition has positive functions, including a means to give alms, close the bound between community members, entertain a family of a deceased, and remember the death.